Formação continuada de professores: tecnologia assistiva para a escola inclusiva de alunos com deficiência visual - Turci, Paulo Cesar (Universidade Federal de São Carlos, 2019)
Abstract: Since 2007, the Ministry of Education and Culture (MEC) has started to distribute notebooks equipped with assistive technology devices (TA), mainly Dosvox, which allows students with visual impairments (DV) to access the computer. However, this inclusive technology has not been incorporated into such students’s educational process as developed in the common classroom. Specialized literature justifies such absence with the claim that the regent teachers have not been prepared during their initial and continued training to work with students with DV and yet neither with notebooks equipped with Dosvox or with other AT devices. In view of the above, the present research has as general objective: to elaborate, apply and analyze a continuous training program aimed at training teachers to work with a computer equipped with assistive technology devices: Windows access facility or Dosvox system in the educational process of students with visual impairment, developed in the common classroom. And as specific objectives: a) Analyze the effects of a continuing training program on the educational process of participants about assistive technology devices: Windows access facility or Dosvox system. B) Analyze in which tasks of continuous training program aimed at educational process of students with visual impairment developed in the common classroom obtained the highest and lowest levels of acquisition of knowledge by the participants. For this purpose, a program evaluation study was carried out, with an AB type design, with four participants: an elementary school teacher, a high school teacher, a retired teacher and a Special Education undergraduate student. The program was composed of 18 tasks divided in six phases with 30 hours of duration with two-hour weekly classes and held in the Community Library (BCO) of the Federal University of São Carlos (UFSCar) in São Carlos. The instruments used to collect data were: a) semi-structured interview with the purpose of characterizing the participants; b) a task protocol to assess the knowledge acquired by participants at two different times: 1) before the start of the program (pre-intervention) and 2) after the completion of the program (post intervention); and c) field diary to register the development of the program. Data analysis was quantitative and occurred as follows: the data obtained with the pre-intervention applied task protocol were compared with the data obtained with the post-intervention task protocol. Results indicated that the participants: Maria, Cristina and Silvia obtained an excellent level of knowledge acquisition during the execution of the program, while the participant John reached a level of regular acquisition. In addition, the female participants were able to use educational strategies structured by the accessibility produced by the above mentioned TA devices, disseminated during the training program, as well as to adapt them to develop new inclusive educational practices in coherence with the educational reality of the school where they used to teach.
Continuing teacher education: assistive technology for the inclusive school for students with visual impairment
Keywords: Educação especial; Tecnologia assistiva; Alunos com deficiência visual; Formação continuada de professores; Dosvox; Special education; Assistive technology; Students with visual impairment; Continuing teacher training; CIENCIAS HUMANAS::EDUCACAO